Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Online di Lazada (Survey Pada Konsumen di Kota Padang) - Fitria Ridha Ningsih; Eri Besra (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
This study aims to analyze the factors that influence consumers' online purchasing decisions at Lazada, namely perceived convenience, perceived benefits, and trust in online purchasing decisions at Lazada. The analytical method used in this research is structural equation modeling using the Smart PLS 2.0 program. This study used 165 respondents as the research sample. The independent variables consist of Perceived Convenience (X1), Perceived Benefits (X2), and Trust (X3), while the dependent variable is Online Purchase Decision (Y). The results of this study indicate that Perceived Convenience, Perceived Benefits, and Trust have a significant influence on Online Purchase Decisions of Lazada consumers in the city of Padang. Keywords: Perceived Convenience, Perceived Benefits, Trust, and Online Purchasing Decisions